(untitled) (Revista LIDER, 2020)
This article summarises the neo-classic industrial location theory. Industrial location theory is a spatial extension of neo-classical microeconomic models (where territory is not explicitly considered). These spatial extensions have been developed by different ways. So, there are location models based in a economic theory of partial equilibrium; others are based in general equilibrium; others in perfect competition etc. Some of the models also have important limitations. The last models, developed for the New Economic Geography do not have some of these limitations. In this sense, they have intensively used concept like externalities that have opened, possibly too much, its meaning.